PHYSIOLOGICAL INDICES OF CHICKENS-BROILERS AFTER INTERNAL APPLICATION OF MINERAL COMPLEX MG++ IN TERMS OF ECONOMY - Бердник, В. П.; Бублик, О. О.; Марченко, Т. М.; Щербак, В. І.; Трирог, О. Г. (Scientific Progress & Innovations, 2017)
Given results of test on 537 chickens-broilers (635 of control) in terms of economy drug produced on the basis of the solution of Poltava bishofit (SPB). Drug was given chickens-broilers of 5-day age group method internally with water in 3 cycles of 24-hour intervals over 7 times in each cycle and 7-day interval between cycles. The chicks, which were given the drug, compared with the control, had a greater average live weight of the body in 43-day age of 50 g, 73-day – 128 g and 111-day – 103 g it shows its positive effect on organisms of chicks up to 2,5 months (time of observations) after the last application in 38-th days of their lives. The drugs based on the SPB will have greater efficiency in the application of the repair chicks and adult hens, i.e. those who live more than 2,5 months. The 43-day age 16 broiler died of the calculation of the initial total number (2,9 %) in experimental group and 30 (4,72 %) in the control. On control broilers, compared with research, savings on the drug, which is not used, and smaller amounts of used feed, but we received much more losses due to lower increases in live body weight and more fatalities. The total value of the economic benefits of the drug only to 43-day age of chicks is 5,8 UAH on each invested 1 UAH.